2019
DOI: 10.1007/s42452-019-0496-2
|View full text |Cite
|
Sign up to set email alerts
|

Finite element method analysis of fibre-metal laminates considering different approaches to material model

Abstract: In this work, different approaches to fibre-metal laminates modelling are presented. Micromechanical, mesomechanical and macromechanical models are discussed. The application of these approaches for exemplary fibre-metal laminate made of aluminium and epoxy resin/glass fibre layers are shown. The classical laminate theory was used to obtain engineering constants for the macroscopic solid model and Puck criterion to obtain material data about epoxy resin/glass fibre layer. Various simulations using different si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…Apart from experimental studies, numerous analytical studies have been reported for analyzing the performance of SACE. Finite element-based modeling has been proven to be a successful method for analyzing the different processes by disintegrating the problems into simpler and smaller elements [30][31][32][33][34][35]. Bhondwe et al [34] established a FEM-based 2D thermal model for predicting the MRR by observing the temperature fields within the work material.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from experimental studies, numerous analytical studies have been reported for analyzing the performance of SACE. Finite element-based modeling has been proven to be a successful method for analyzing the different processes by disintegrating the problems into simpler and smaller elements [30][31][32][33][34][35]. Bhondwe et al [34] established a FEM-based 2D thermal model for predicting the MRR by observing the temperature fields within the work material.…”
Section: Introductionmentioning
confidence: 99%
“…Identifying the nature of failure stress and mode of failure (matrix or fiber) are also the features of stress-strain analysis [20]. Different failure criteria are proposed in the literature and in the present work strengthbased theories of failure are considered to identify the FPF [11,13,20]. These are briefly presented below.…”
Section: Review Of Failure Analysismentioning
confidence: 99%
“…A shear deformable finite element (FE) method was used to estimate the FPFs for laminates with different stacking sequences. The developed procedure is compared with the exact solution for various failure criterion [13]. In the similar way a 3D layer wise mixed FE model for thick composite laminated plates has been proposed to predict the FPF.…”
Section: Introductionmentioning
confidence: 99%
“…Solving the simultaneous equation [Eqs. (20) and (21)] to find the unknowns and substitute back to Eq. (17).…”
Section: Application Of Galerkin Of Weighted Residual To the Governinmentioning
confidence: 99%
“…Galerkin of weighted residual handles circular plate vibration problem without any manipulation of governing equation with very precise results compared to experimental with few iterations. Other recent publications reported on vibration are [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 97%